The First WHO International Standard for Harmonizing the Biological Activity of Bevacizumab - Haiyan Jia; Parvathy Harikumar; Eleanor Atkinson; Peter Rigsby; Meenu Wadhwa (Biomolecules, 2021)
Several Bevacizumab products are approved for clinical use, with many others in late-stage clinical development worldwide. To aid the harmonization of potency assessment across different Bevacizumab products, the first World Health Organization (WHO) International Standard (IS) for Bevacizumab has been developed. Two preparations of a Bevacizumab candidate and comparator were assessed for their ability to neutralize and bind vascular endothelial growth factor (VEGF) using different bioassays and binding assays in an international collaborative study. Relative potency estimates were similar across different assays for the comparator or the duplicate-coded candidate sample. Variability in relative potency estimates was reduced when the candidate standard was used for calculation compared with various in-house reference standards, enabling harmonization in bioactivity evaluations. The results demonstrated that the candidate standard is suitable to serve as an IS for Bevacizumab, with assigned unitages for VEGF neutralization and VEGF binding activity. This standard coded 18/210 was established by the WHO Expert Committee on Biological Standardization, which is intended to support the calibration of secondary standards for product development and lifecycle management. The availability of IS 18/210 will help facilitate the global harmonization of potency evaluation to ensure patient access to Bevacizumab products with consistent safety, quality and efficacy.